Application of Monte Carlo analytic hierarchical process (MCAHP) in the prioritization of theme park service quality elements - Banzon, Mc Joren R. (Animo Repository, 2016)
Previous studies around the globe regarding the factors affecting customer satisfaction in theme parks had plainly used multiple linear regression and statistical analysis in order to arrive at a conclusion. This study will course on creating a model that will determine the same matter in the Philippine setting through the application of the Analytic Hierarchical Process (AHP). Accordingly, the Monte Carlo Simulation will be used in order to prioritize the factors of theme park customer satisfaction. This model will give aid to the management of both theme and amusement parks in the Philippines in prioritizing the factors deemed important by the costumers. The model in general is expected to be applicable to the service industry and will be beneficial to various service enterprises through the improvement of their decision making process. © IEOM Society International. © IEOM Society International.